2018
DOI: 10.1111/imb.12387
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of microRNA miR‐2b‐3p in regulation of metabolic resistance to insecticides in Plutella xylostella

Abstract: The diamondback moth, Plutella xylostella, has developed extremely high levels of resistance to chlorantraniliprole and other classes of insecticides in the field. As microRNAs (miRNAs) play important roles in various biological processes through gene regulation, we examined the miRNA profile of P. xylostella in response to chlorantraniliprole exposure. RNA sequencing analysis showed that insecticide treatment caused significant changes in the abundance of some miRNAs. Increasing exposure time and insecticide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
48
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 56 publications
3
48
0
Order By: Relevance
“…Arthropods continue to damage agricultural commodities and vector diseases threatening human welfare due to ongoing challenges in pest control that arise from instances where selection has caused high levels of resistance following repeated exposures to insecticidal agents. The involvement of miRNAs in the regulation of metabolic resistance to insecticides has been suggested via comparative and correlative studies for pyrethroids 29 and ryanoids 30 , but strong evidence for miRNAs as causative factors among these resistant phenotypes is arguably lacking. The present study demonstrated that members for the miR-310s cluster interact with target binding sites within 3ʹ-UTR sequences of cytochrome P450, thereby regulating transcript levels in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Arthropods continue to damage agricultural commodities and vector diseases threatening human welfare due to ongoing challenges in pest control that arise from instances where selection has caused high levels of resistance following repeated exposures to insecticidal agents. The involvement of miRNAs in the regulation of metabolic resistance to insecticides has been suggested via comparative and correlative studies for pyrethroids 29 and ryanoids 30 , but strong evidence for miRNAs as causative factors among these resistant phenotypes is arguably lacking. The present study demonstrated that members for the miR-310s cluster interact with target binding sites within 3ʹ-UTR sequences of cytochrome P450, thereby regulating transcript levels in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has shown that overproduction of detoxification enzymes is an important mechanism for insecticide resistance and complex regulatory mechanisms are involved in the up‐regulated expression of resistance‐associated detoxification genes, such as cis ‐regulatory elements and/or trans ‐acting factors, microRNAs and GPCR signaling cascades . The up‐regulation of CYP6FU1 conferring deltamethrin resistance in Laodelphax striatellus involves multiple cis ‐regulatory elements .…”
Section: Discussionmentioning
confidence: 99%
“…Caterpillars of the diamondback moth, Plutella xylostella , are highly destructive pests of Brassica crops [ 58 ]. Several miRNA species that regulate resistance to the ryanoid insecticide chlorantraniliprole were identified in this insect [ 59 ]. miR-2b-3p and miR-14b-5p post-translationally suppress two cytochrome P 450 monooxygenase genes, CYP9F2 and CYP307a1 , respectively, which are most likely involved in insecticide detoxification [ 59 ].…”
Section: Plant-insect Interactionsmentioning
confidence: 99%
“…Several miRNA species that regulate resistance to the ryanoid insecticide chlorantraniliprole were identified in this insect [ 59 ]. miR-2b-3p and miR-14b-5p post-translationally suppress two cytochrome P 450 monooxygenase genes, CYP9F2 and CYP307a1 , respectively, which are most likely involved in insecticide detoxification [ 59 ]. A diet containing miR-2b-3p mimics provided to a P. xylostella line resistant to the pyrethroid insecticide deltamethrin results in greater lethality, presumably because miRNA-mediated suppression of cytochrome P 450 enzyme decreases the insect ability to detoxify the pesticide.…”
Section: Plant-insect Interactionsmentioning
confidence: 99%